TEACHER’S ROLE AS REFLECTED IN WHIPLASH MOVIE - Muhammad Romadhon Tri Wahyu Aji; Adria Vitalya Gemilang; Isti'anatul Hikmah (Wiralodra English Journal, 2022)
Teachers’ role in a class is fascinating because their existence may affect students’ behaviors due to their interaction regularly. The portrait of such situation was adapted into movies, one of them was Whiplash movie directed by Damien Chazelle. The Whiplash movie was utilized as the source of the data in this study. Therefore, the aim of this study is to identify the role of the teacher in the Whiplash movie specifically in classroom activities by employing a qualitative method. It was used to collect and analyze the data. Furthermore, the data were taken from the subtitle of the movie focusing on the classroom’s activities scenes, consequently, the data analyzed were in the form of utterances. The gathered data were analyzed using the teacher’s roles theory proposed by Harmer (2001). The results showed that Mr. Fletcher, a teacher in the Whiplash movie, has eight characteristics including controller, organizer, assessor, prompter, participant, resource, tutor, and observer. Those characteristics refer to the teacher’s learning style that influenced students’ behaviors a lot.